2018
DOI: 10.1080/10413200.2018.1433250
|View full text |Cite
|
Sign up to set email alerts
|

Educating and Supporting Tennis Parents Using Web-Based Delivery Methods: A Novel Online Education Program

Abstract: This study evaluated the effectiveness of a novel online education program for British tennis parents and their experiences of engaging in the program. Using a convergent parallel mixedmethods design, 13 parents completed pre-and post-program online questionnaires, while a subset of 9 participants also shared their experiences via an asynchronous email interview. Quantitative findings revealed positive directional changes for almost all of the variables in relation to emotional experiences, goal orientations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 30 publications
4
74
0
Order By: Relevance
“…This shows similarities to other review work exploring the meta-theoretical underpinnings of sport science research (North, 2013a). From the studies drawing on pragmatism, Thrower et al (2019) engaged in the most thorough methodological discussion, justifying the mixed methods strategy on the basis of complementarity, the capacity to generate new insight, and utility for practitioners. Rumbold et al (2018) also addressed the methodological justifications for MMR and described their work as "a pragmatist perspective with a critical realist ontology" (p. 28), whereas Jackman et al 2017noted that MMR is a contested terrain and explained that "a pragmatic stance to the use of mixed methods (…) was adopted" (p. 115).…”
Section: Paradigmatic Positioning Of Mmrmentioning
confidence: 52%
See 1 more Smart Citation
“…This shows similarities to other review work exploring the meta-theoretical underpinnings of sport science research (North, 2013a). From the studies drawing on pragmatism, Thrower et al (2019) engaged in the most thorough methodological discussion, justifying the mixed methods strategy on the basis of complementarity, the capacity to generate new insight, and utility for practitioners. Rumbold et al (2018) also addressed the methodological justifications for MMR and described their work as "a pragmatist perspective with a critical realist ontology" (p. 28), whereas Jackman et al 2017noted that MMR is a contested terrain and explained that "a pragmatic stance to the use of mixed methods (…) was adopted" (p. 115).…”
Section: Paradigmatic Positioning Of Mmrmentioning
confidence: 52%
“…In terms of evaluating research rigour, some researchers addressed integrative quality criteria that they framed as applicable to the study as a whole (e.g., Karageorghis et al, 2018;Mallinson-Howard et al, 2018;Rumbold et al, 2018;Thrower et al, 2019), but more often quantitative and qualitative parts of the study were evaluated separately (e.g., Kacperski & Hall, 2017;Middleton et al, 2017;Redwood-Brown et al, 2018;Richard et al, 2017;Whitehead et al, 2018). From the integrative perspective, Thrower et al (2019) suggested that "taken as a whole, this study can be judged on the capacity to which it is relevant for the research questions, is transparent, has a rationale for using mixed methods, and requires the integration of mixed-method findings", while at the same time maintaining that "the quality criteria for each aspect of the study should be considered separately" (p. 4). Mallinson-Howard et al (2018) drew on Tracy's (2010) eight "universal" criteria (which were originally introduced as guidelines for qualitative researchers) to make a judgement about the quality of their MMR study of experiences associated with different types of perfectionism.…”
Section: Considerations Of Research Qualitymentioning
confidence: 99%
“…In including countries with well-established structures and policies required to assist athletes and others with fragmented dual career policies [ 29 ], this research work advances the academic knowledge and provides broad insights into the parents’ views and perceptions regarding their educational request for optimizing their relevant role in support of dual career athletes competing in different sports. In fact, a sound understanding of the actual rather than assumed needs for parental support is essential to generate bespoke guidelines for the organization of customer-based dual career education programmes for parents [ 47 , 60 ]. In the current work, the interaction between parents from several sport contexts indicated that the collective view of parent’s needs of education concerns several aspects of dual career, highlighting the complexity of the parental role in supporting student-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing from Bronfenbrenner's (2005) bioecological theory, it is clear that much of our research on sport parents has existed within the ecological microsystem -the ecological niche or context that is closest to directly influencing the child. However, microsystems comprising coaching or parental attitudes and behaviour are influenced by a series of more distal outer systems or contexts (see Holt, Tamminen, Black, Sehn, & Wall, 2008) including mesosystems and exosystems (e.g., restrictions on parental involvement due to work pressures/culture; how a coach is evaluated in his/her job environment by an employer; how parents are perceived by coaches and administrators within different delivering intentional group-based or online sport parent interventions (i.e., Dorsch, King, Dunn, Osai, & Tulane, 2017;Thrower, Harwood, & Spray, 2018) through improvements in parental confidence, task-orientated parent-child communication, support, and warmth. However, although such initial findings are important in the context of relational factors that underpin a PYD climate (Holt et al, 2017), interventions with parents targeting specific 'in situ' (e.g., enjoyment, reduced anxiety, focus) and long-term child developmental outcomes (e.g., enhanced confidence, emotional regulation and coping skills, communication skills, self-awareness, leadership) are necessary.…”
Section: The Next Years: Challenging Systems and Improving Policiesmentioning
confidence: 99%